2017
DOI: 10.1111/bph.13698
|View full text |Cite
|
Sign up to set email alerts
|

miR‐15b mediates oxaliplatin‐induced chronic neuropathic pain through BACE1 down‐regulation

Abstract: These findings suggest that miR-15b contributes to oxaliplatin-induced chronic neuropathic pain at least in part through the down-regulation of BACE1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Recently, increasing studies have observed the roles of non‐coding RNAs in neuropathic pain (Ito et al, ; Su et al, ; Zhou, Xiong, Chen, Yang, & Fan, ). In our present study, we observed that XIST/miR‐544/STAT3 axis was responsible for neuropathic pain progression in CCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing studies have observed the roles of non‐coding RNAs in neuropathic pain (Ito et al, ; Su et al, ; Zhou, Xiong, Chen, Yang, & Fan, ). In our present study, we observed that XIST/miR‐544/STAT3 axis was responsible for neuropathic pain progression in CCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic paclitaxel produced ectopic spontaneous activity in DRG neuronal somata . This abnormal activity, which has been identified as a CIPNP contributor, may be related to the changes in the gene expression at the transcriptional and translational levels in the DRG after chemotherapy drug treatments . Understanding how chemotherapy drugs drive these changes is essential for improving patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] This abnormal activity, which has been identified as a CIPNP contributor, [10][11][12][13] may be related to the changes in the gene expression at the transcriptional and translational levels in the DRG after chemotherapy drug treatments. [10][11][12][13][14][15][16][17][18][19] Understanding how chemotherapy drugs drive these changes is essential for improving patient care.…”
Section: Introductionmentioning
confidence: 99%
“…6 For instance, miR-15b was reported to mediate neuropathic pain via downregulating BACE1. 7 The upregulation of miR-132-3p was correlated to chronic neuropathic pain. 8 Since miRNA has become the target of neuropathic pain therapy, it is of great value to find novel targets for neuropathic pain treatment.…”
Section: Introductionmentioning
confidence: 99%